2009
DOI: 10.1007/s11738-009-0423-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zinc on the growth and physiological and biochemical parameters in seedlings of Eruca sativa (L.) (Rocket)

Abstract: Eruca sativa seedlings were treated with different Zn concentrations (0, 250, 500, 1,000, 2,000 lg g -1 dried growth medium) under controlled conditions. The seedlings were harvested 20 days after Zn treatment. Physiological parameters, such as root and shoot length, fresh and dry weight, were measured and Zn content of roots and shoots was determined. Furthermore, various biochemical parameters were studied on E. sativa leaves: enzymatic antioxidants, such as superoxide dismutase (SOD), catalase (CAT), guaiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 42 publications
8
22
0
Order By: Relevance
“…In this study, SOD activity decreased in all Cd concentrations when compared with that of the control but the decrease in 450 µg • g -1 was significant statistically. Similarly, it was reported in the other researches that SOD activity decreased in toxic concentrations of some heavy metals [13,29]. Cd is a redox inactive metal and it has no direct effect on the SOD activity.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In this study, SOD activity decreased in all Cd concentrations when compared with that of the control but the decrease in 450 µg • g -1 was significant statistically. Similarly, it was reported in the other researches that SOD activity decreased in toxic concentrations of some heavy metals [13,29]. Cd is a redox inactive metal and it has no direct effect on the SOD activity.…”
Section: Discussionsupporting
confidence: 71%
“…The analysis showed that lipid peroxidation, the most distinctive indication of oxidative stress, increased due to the increase in cadmium concentration. A similar responses were observed in plants treated with Cd and the other heavy metal [29,32,35]. The enzymes, such as SOD, CAT, PODx are considered to play an important role in the cellular defense mechanisms against ROS caused by heavy metal toxicity.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Leaf and root tissues of the mandarin plants, subjected to Zn-deficiency and -excess, generated AsA in lower quantity (Fig. 5a) probably due to higher activity of APX, which along with AsA are the components of Halliwel-Asada pathway (Ozdener and Aydin 2010). In our study, starch contents dwindled in the Zn-deficient and Zn-toxic plants (Fig.…”
Section: Discussionmentioning
confidence: 46%
“…Many studies have indicated that PCD plays a role in the developmental plasticity of plant architecture (Duan et al, 2010). Excess Zninduced growth inhibition and root death have been found in various plant species (Lingua et al, 2008;Ozdener and Aydin, 2010). However, whether Zninduced root death occurs through PCD and its underlying mechanisms are poorly understood.…”
mentioning
confidence: 99%